Penguatan Pendidikan Karakter di Sekolah Menengah Kejuruan - Aries Abbas; Marhamah Marhamah (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
This research began from the emergence of character problems or character crisis by shifting the students’ ethics values in the school. Where the students don’t respect teachers and friends, there is brawl among students, even violence occurs in the classroom, this is a threat of disintegration of the nation. The formulation of the problem is how the strengthening strategy of character education. The purpose of this research is to know the strengthening strategy of character education in the school, related to implementation, monitoring evaluation, supporting factors, obstacles and obtained result. The research method used qualitative approach on natural subject or natural setting, by using observation data collection techniques, interviews and documentation, data analysis techniques through data reduction, verification and took a conclusions of processed data. The research was held at SMK 45 and SMK IT NU Saguling, West Bandung. The result of this study. Students become intent on strengthening the character education activities, responsive to social activities in the society, although not all students can implement it yet. The level of discipline is good because students feel shy if they aren’t disciplined, the result of the shame cultural, some students who used to come late to be in time even though not all students feel ashamed when coming late. The supporting factors the implementation of the strengthening of character education in the schools is a good strategy from the principal, the committee and a team of the parent class of students. The Obstacle factors, the shame culture is not held in the school yet, not all teachers become a role models in the schools who give good examples for students. Not all teacher become a strong and intelligent character. So that the presence of educators is as a key actor in the learning process, a professional and have a strong and intelligent character must really have atmosphere in the school, because through educators who have strong and intelligent character will create human resources which is a reflection of a nation that has strong and intelligent character, and virtuous morals.Penelitian ini berawal dari munculnya permasalahan karakter atau krisis karakter dengan menggeser nilai-nilai etika siswa di sekolah. Dimana siswa tidak menghargai guru dan teman, terjadi tawuran antar siswa, bahkan terjadi kekerasan di dalam kelas, ini menjadi ancaman disintegrasi bangsa. Rumusan masalah adalah bagaimana strategi penguatan pendidikan karakter. Tujuan dari penelitian ini adalah untuk mengetahui strategi penguatan pendidikan karakter di sekolah terkait dengan pelaksanaan, evaluasi monitoring, faktor pendukung, kendala dan hasil yang diperoleh. Metode penelitian yang digunakan pendekatan kualitatif pada subjek alam atau setting alam, dengan menggunakan teknik pengumpulan data observasi, wawancara dan dokumentasi, teknik analisis data melalui reduksi data, verifikasi dan pengambilan kesimpulan dari data olahan. Penelitian dilaksanakan di SMK 45 dan SMK IT NU Saguling, Bandung Barat. Hasil penelitian ini. Siswa berkeinginan kuat untuk memperkuat kegiatan pendidikan karakter, tanggap terhadap kegiatan sosial di masyarakat, meskipun belum semua siswa dapat melaksanakannya. Tingkat kedisiplinannya baik karena siswa merasa malu jika tidak didisiplinkan akibat adanya budaya malu, sebagian siswa yang dulunya terlambat datang tepat waktu padahal tidak semua siswa merasa malu jika datang terlambat. Faktor pendukung pelaksanaan penguatan pendidikan karakter di sekolah adalah strategi yang baik dari kepala sekolah, komite dan tim kelas orang tua siswa. Faktor penghambatnya, belum adanya budaya malu di sekolah, belum semua guru menjadi panutan di sekolah yang memberikan keteladanan yang baik bagi siswa. Tidak semua guru menjadi karakter yang kuat dan cerdas. Sehingga keberadaan pendidik sebagai aktor kunci dalam proses pembelajaran, seorang yang profesional dan berkarakter kuat dan cerdas haruslah benar-benar memiliki atmosfir di sekolah, karena melalui pendidik yang berkarakter kuat dan cerdas akan tercipta sumber daya manusia yang merupakan cerminan. bangsa yang memiliki karakter kuat dan cerdas, serta berakhlak mulia.